Silicon-carbon nano-composite negative electrode active material and preparation method and application thereof

By using silicon-carbon nanocomposites with nano-silicon spheres as the core in lithium-ion batteries, the volume expansion and explosion risks of negative electrode active substances during charging and discharging are solved, the capacity, efficiency and stability of the battery are improved, and the battery performance is achieved.

CN120527375AInactive Publication Date: 2025-08-22HUNAN ASTRA TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510985893.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-08-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative active substances of existing lithium-ion batteries (LIBs) have a risk of large volume expansion, poor cycle stability and explosion during charging and discharging, and the existing mixing ratio limitations lead to limited battery performance.

Method used

A silicon-carbon nanocomposite material with nano-silicon spheres as the core and coated with a multi-layer carbon layer structure is used to control the particle size and carbon layer thickness to inhibit the volume expansion of silicon and improve conductivity and stability.

Benefits of technology

The volume expansion rate of silicon is significantly reduced, and the battery capacity, battery efficiency, energy density, thermal stability and current retention rate are improved, achieving higher battery performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120527375A_ABST
    Figure CN120527375A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon nano negative electrode active material and a preparation method and application thereof. The silicon-carbon nano negative electrode active material comprises a silicon core and a conductive inhibition layer coating the surface of the silicon core, the silicon core is a nanometer silicon ball, and the conductive inhibition layer is a carbon layer. The silicon-carbon nano negative electrode active material provided by the invention realizes the effects of remarkably reducing the volume expansion rate of silicon to be within 30%, remarkably improving the battery capacity, battery efficiency, energy density, thermal stability, current retention rate and the like, and can be widely applied to lithium secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a high-capacity LIB silicon-carbon nanometer negative electrode active material. Background Art

[0002] Lithium-ion batteries (LIBs) are commonly used as energy sources for portable electronic devices, electric vehicles, and other applications. Current technology is limited in the development of efficient silicon anode active materials. The key lies in coating the silicon surface with graphite or graphene to reduce the risk of explosion caused by ion exchange heat during LIB charging and discharging.

[0003] However, all existing negative electrode active materials have a particle size exceeding 100 nanometers, and to reduce the risk of LIB explosion, their mixing ratio in the negative electrode material (based on a graphite unit of 100) is limited to 3% to 5%. However, even a slight variation in this limited mixing ratio (±0.1%) can lead to a fatal explosion risk in LIBs.

[0004] Therefore, global negative electrode active material manufacturers continue to devote themselves to the research and development of new silicon negative electrode active materials with the following characteristics: elimination of explosion risk; higher capacity; longer charge and discharge cycle life; and better cost performance.

[0005] Currently known silicon anode active materials can expand in volume (up to 300%) during LIB charge and discharge due to ion exchange, potentially causing explosions. Furthermore, the polar decomposition reaction of the ion exchange electrolyte continuously destabilizes the surface of silicon particles and forms an oxide film at the electrolyte interface (SEI), reducing charge and discharge cycle durability.

[0006] Therefore, there is an urgent need for innovative development of the following technologies: inhibiting the volume expansion of silicon during charging and discharging; improving capacity, efficiency and energy density; and improving thermal stability and current retention. Summary of the Invention

[0007] The present invention aims to address the aforementioned problems of the prior art by providing a battery negative electrode active material (i.e., a silicon-carbon nanocomposite negative electrode active material) that exhibits reduced volume expansion during battery charge and discharge while simultaneously exhibiting excellent capacity, battery efficiency, energy density, thermal stability, and current retention. The present invention also aims to provide a method for preparing the battery negative electrode active material, enabling the preparation of a novel negative electrode active material that can be applied in actual production.

[0008] To achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a silicon-carbon nanometer negative electrode active material, comprising a silicon core and a conductive inhibition layer coated on the surface of the silicon core; the silicon core is a nano-silicon ball, and the conductive inhibition layer is a carbon layer.

[0009] Furthermore, the carbon layer has a multi-layer carbon layer structure.

[0010] Furthermore, the number of the multi-layer carbon layer is 10 to 25 layers.

[0011] Furthermore, the material of the multi-layer carbon layer is at least one of carbon, graphite, and graphene.

[0012] Furthermore, the material of a layer close to the core of the multi-layer carbon layer is carbon or graphite, and the remaining carbon layers are graphene layers.

[0013] Furthermore, each carbon layer in the multi-layer carbon layer is independently a porous layer or a non-porous layer.

[0014] Furthermore, the particle size of the nano-silicon spheres is less than 100 nm, preferably 10-50 nm.

[0015] In a second aspect, a method for preparing a silicon-carbon nano-anode active material is provided, comprising: (a) In a reactor containing a solvent and an inert gas atmosphere, a transient high voltage exceeding 25,000 V and lasting no longer than 1 / 100 second is applied to both ends of a silicon wire. a1. Preparation of nano-silicon particles by instantaneous expansion; a2. Coating carbon on the surface of the prepared nano-silicon particles to prevent expansion, thereby obtaining a silicon-carbon nanocomposite material; (b) a step of classifying the silicon-carbon nanocomposite material produced above; (c) heating and drying the silicon-carbon nanocomposite material; (d) performing a vacuum heat treatment on the silicon-carbon nanocomposite material; (e) a step of crushing and disintegrating the silicon-carbon nanocomposite material.

[0016] In an embodiment of the present invention, the solvent comprises an alcohol, N-methyl-2-pyrrolidone (NMP), and a surfactant. Furthermore, in the solvent, the N-methyl-2-pyrrolidone (NMP) accounts for 5 to 20% by weight of the total alcohol, and the surfactant accounts for 2 to 10% by weight of the total alcohol.

[0017] The material produced by the above-mentioned preparation process comprises a core formed of silicon nanoparticles as a negative electrode active material, and a conductive layer formed of a carbon material further coated on the core. The particles are spherical in shape, and the particle size is strictly controlled to be less than 100 nanometers, and more preferably less than 50 nanometers.

[0018] In a third aspect, a negative electrode active material is provided, comprising the aforementioned silicon-carbon nanometer negative electrode active material or the silicon-carbon nanometer negative electrode active material prepared by the aforementioned preparation method.

[0019] In a fourth aspect, a negative electrode is provided, comprising the aforementioned negative electrode active material.

[0020] According to a fifth aspect, a secondary battery is provided, comprising the aforementioned negative electrode.

[0021] In a sixth aspect, a battery pack is provided, comprising the aforementioned secondary battery.

[0022] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The silicon-carbon nanometer negative electrode active material provided by the present invention reduces the volume expansion rate of silicon by 10 times in existing lithium-ion batteries. Compared with pure graphene, it has twice the battery specific capacity, three times the battery first coulombic efficiency, five times the energy density, three times the thermal stability and twice the current retention rate.

[0023] The preparation process of the silicon-carbon nanocomposite active material provided by the present invention can realize the large-scale production of silicon-carbon nano negative electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 This is the SEM image of the silicon-carbon nanocomposite material prepared in Example 1.

[0026] Figure 2 This is a TEM image of the silicon-carbon nanocomposite material prepared in Example 1. DETAILED DESCRIPTION

[0027] In response to the technical problems that existing silicon negative electrode active materials have huge volume expansion and pulverization problems during the charge and discharge process, resulting in poor cycle stability and easy explosion, the applicant has developed a new type of silicon-carbon nanometer negative electrode active material after extensive research. It can not only significantly inhibit the volume expansion of silicon during charge and discharge, improve capacity, efficiency and energy density, but also improve thermal stability and current retention rate. Based on this, the present invention was completed.

[0028] Some embodiments of the present invention provide a silicon-carbon nano-negative electrode active material having a core-shell structure, comprising a silicon core and a conductive inhibition layer coated on the surface of the silicon core; the silicon core is a nanoporous silicon sphere, and the conductive inhibition layer is a carbon layer.

[0029] The huge volume change (about 300% expansion) of silicon materials during battery charging and discharging leads to the generation of electrode cracks. In the silicon-carbon nano-negative electrode active material provided by the present invention, nanoporous silicon balls are used as the core. The nano-scale silicon particles not only significantly alleviate the volume change during the charging and discharging process and reduce particle breakage, but also significantly shorten the lithium ion diffusion path, accelerate ion and electron transmission, and improve the rate performance. The spherical morphology can further improve the processing performance and mechanical properties of the electrode material and improve the rate performance of the battery. Due to the good fluidity of the spherical morphology, it can be evenly dispersed during the preparation of the electrode slurry, improving the uniformity and consistency of the electrode. At the same time, the spherical silicon powder enables it to remain relatively stable during the charging and discharging process, which helps to improve the rate performance of the battery, that is, under high current charging and discharging conditions, the battery still It can maintain good performance; the carbon layer coated on the surface of the nano-spherical silicon particles can not only significantly inhibit the volume expansion of the silicon matrix, prevent the silicon particles from breaking and agglomerating, thereby improving the cyclic stability of the material, specifically, the conductive inhibition layer carbon layer of the present invention can significantly reduce the expansion of the core layer, thereby inhibiting explosion and improving battery performance, and the coating of the carbon layer can significantly improve the conductivity of the composite material and promote the transmission of electrons; at the same time, it can also prevent direct contact between the electrolyte and the silicon surface, reduce the occurrence of side reactions, thereby facilitating the formation of a stable and uniform solid electrolyte interface (SEI) film, reducing the specific surface area of ​​the silicon particles, reducing surface activity, and reducing the decomposition and consumption of the electrolyte. Based on the above reasons, the silicon-carbon nano-negative electrode active material provided by the present invention achieves the effects of significantly reducing the volume expansion rate of silicon and significantly improving battery capacity, battery efficiency, energy density, thermal stability and current retention rate.

[0030] In some preferred embodiments, the carbon layer has a multilayer carbon layer structure. This multilayer carbon layer structure not only effectively suppresses silicon core expansion but also significantly improves electrical conductivity. Furthermore, preferably, the multilayer carbon layer has 10 to 25 layers, such as 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, and the like. The conductive layer comprises multiple layers (10 to 25 layers) exhibiting a variety of properties. The shape and structure of the silicon-carbon nanocomposite can be adjusted by controlling the reaction conditions in the reactor during the preparation method.

[0031] In some preferred embodiments, the multi-layer carbon layer is made of at least one of carbon, graphite, and graphene.

[0032] In some preferred embodiments, each carbon layer in the multi-layer carbon layer can be independently a porous layer or a non-porous layer.

[0033] In some preferred embodiments, in the multilayer carbon layer, the material of a layer near the core of the multilayer carbon layer is carbon or graphite, and the remaining carbon layers are graphene layers. The thickness of the carbon or graphite layer near the core is thicker, and the carbon is more tightly bonded to the silicon substrate than the graphene layer, which can reduce interface defects. The interlayer slip characteristics of the graphene layer can effectively buffer the volume expansion of silicon during charge and discharge or thermal cycling, and have a good buffering effect on stress. The external multi-graphene layer has excellent electrical conductivity, chemical stability and high strength. Therefore, the multilayer carbon layer having an internal material of carbon or graphite and an external graphene layer not only has a good bonding effect with the silicon core, but can better alleviate the expansion of the silicon core, and has a good electrical conductivity, which is conducive to the significant volume expansion effect, structural stability, electrochemical stability and electrical properties of the nano-silicon-carbon composite active material. The internal carbon layer is carbon or graphite, and the external graphene layer can be independently porous or non-porous. Optionally, the multilayer graphene layers are stacked adjacent to each other, and the carbon atoms of the adjacent two layers of graphene can be AB stacking, AA stacking or twisted stacking.

[0034] In some preferred embodiments, the particle size of the nano-silicon spheres is less than 100 nm, preferably 10-50 nm. Compared to existing silicon negative electrode active materials, which typically have particle sizes exceeding 100 nm, silicon spheres with particle sizes below 100 nm, especially those in the nanometer range of 10-50 nm, can significantly accelerate ion / electron transport, improve rate performance, and thus enhance fast charging capabilities.

[0035] In some preferred embodiments, the nano-silicon spheres are porous nano-silicon spheres. Porous nano-silicon spheres not only help improve the rate of lithium ion insertion and removal, but also help further alleviate volume expansion and improve structural stability. Porous here refers to having more than two holes, such as two holes, three holes, four holes, five holes, six holes, etc. The multiple pores of the nano-silicon spheres can increase the rate of lithium ion insertion and removal by several times, thereby significantly improving their electrical properties.

[0036] Some embodiments of the present invention provide a method for preparing a silicon-carbon nano-anode active material, comprising: (a) In a reactor containing a solvent and an inert gas atmosphere, a transient high voltage exceeding 25,000 V and lasting no longer than 1 / 100 second is applied to both ends of a silicon wire. a1. Preparation of nano-silicon particles by instantaneous expansion; a2. Coating carbon on the surface of the prepared nano-silicon particles to form a silicon-carbon nanocomposite material that prevents expansion; (b) a step of classifying the silicon-carbon nanocomposite material produced above; (c) heating and drying the silicon-carbon nanocomposite material; (d) performing a vacuum heat treatment on the silicon-carbon nanocomposite material; (e) a step of crushing and disintegrating the silicon-carbon nanocomposite material.

[0037] In an embodiment of the present invention, the solvent includes alcohol, N-methyl-2-pyrrolidone (NMP) and a surfactant.

[0038] When implementing the above step (a) of the present invention, the reactor is a conventional high-voltage electric explosion device, the material placed inside the reactor is silicon wire, and a certain proportion of ethyl or methyl series solution and inert gas such as argon, nitrogen, neon, helium, etc. are injected into the internal space of the reactor. When a high voltage of more than 25,000V is applied to both ends of the wire, the inert gas inside the reactor can be ionized.

[0039] Simultaneously, the silicon wires are vaporized into nanoparticles instantaneously (e.g., within 1 / 1000 of a second). These nanoparticles, along with the carbon that decomposes simultaneously, are then coated on the surface of the nanoparticles. The alcohol component of the solution can be ethanol, methanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, or other alcoholic solvents. By adjusting the ratio of these components, the amount of carbon coating applied to the nanoparticle surface can be precisely controlled.

[0040] The present invention can employ a mixed system of various series of solutions described above. For example, when using an ethyl alcohol solvent and a methyl alcohol solvent, the weight ratio of the ethyl alcohol solvent to the methyl alcohol solvent is preferably approximately 60-80:20-40. When the weight ratio falls within the above numerical range, it affects battery capacity, battery efficiency, energy density, thermal stability, and battery capacity retention.

[0041] Furthermore, when the mixed solution contains isopropyl alcohol, ethyl alcohol, and methyl alcohol, the mass ratio of isopropyl alcohol to ethyl alcohol and methyl alcohol is preferably 100:20-40:5-20.

[0042] The surfactant of the above-mentioned mixed solution is a fatty acid ester of Sorbitan (sorbitan, also known as sorbitan), and Sorbitan Monolaurate (sorbitan laurate, also known as sorbitan monolaurate or sorbitol monolaurate), Sorbitan monopalmitate (sorbitan palmitate, also known as sorbitan monopalmitate or sorbitol monopalmitate), Sorbitan monostearate (sorbitan stearate, also known as sorbitan monostearate or sorbitol monostearate), Sorbitan Monooleate (sorbitan oleate, also known as sorbitan monooleate or sorbitol monooleate), etc. can be used.

[0043] The content of the above-mentioned surfactant is preferably 2 to 10 parts by weight per 100 parts by weight of alcohol, for example, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc., and when the content meets the above numerical range, the battery capacity, battery efficiency, energy density, thermal stability, battery capacity retention rate, etc. can be maximized.

[0044] In addition, polyoxyethylene sorbitan fatty acidester (polyoxyethylene sorbitan fatty acid ester, also known as polyoxyethylene sorbitan fatty acid esters) can be additionally used as the above-mentioned surfactant.

[0045] The fatty acid ester of polyoxyethylene sorbitan ester may be, but is not limited to, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, and the like.

[0046] In some preferred embodiments, the solvent may further contain an acrylate-containing silane coupling agent, and the amount of the silane coupling agent added may be 0 to 12 parts by weight relative to 100 parts by weight of the alcohol. Available acrylate-containing silane coupling agents include 3-Methacryloxypropyl-methyl-Dimethoxy-Silane, 3-Methacryloxypropyl-Trimethoxy Silane, 3-Methacryloxypropyl-methyl-Diethoxy Silane, 3-Methacryloxypropyl-Triethoxy Silane, 3-Acryloxypropyl-Trimethoxy Silane, Methacryloxy-methyl-Triethoxy Silane, Methacryloxy-methyl-Trimethoxy Silane, and the like.

[0047] In step a2, the carbon component of the solvent is coated on the surface of the prepared silicon nanoparticles to produce a silicon-carbon nanocomposite negative electrode active material. The high-energy silicon nanoparticles prepared in step a1 react with the solvent in the reactor, causing the solvent to decompose and ionize, thereby coating the surface of the silicon nanoparticles with a conductive carbon layer.

[0048] At this point, the carbon formed by solvent decomposition can coat the surface of the silicon nanoparticles, forming core-shell structured nanoparticles. These core-shell structured nanoparticles, which serve as silicon-carbon nanocomposite negative electrode active materials, comprise a core composed of silicon and a shell composed of carbon coated on the core.

[0049] Specifically, the invention comprises a core layer composed of silicon from the aforementioned silicon-carbon nanocomposite material; and a conductive layer composed of carbon coated on the core layer. The core layer is composed of crystalline silicon and may have a porous structure containing numerous pores capable of accommodating lithium ions. The conductivity suppresses expansion of the core layer, prevents damage to the core layer, and imparts thermal stability.

[0050] This silicon core layer undergoes significant volume changes (expanding by approximately 300%) during the battery's charge and discharge cycles, which can lead to electrode cracking. Simultaneously, due to the decomposition reaction between lithium ions and the electrolyte, an unstable solid electrolyte interface (SEI) continuously forms on the surface of the silicon particles. As the charge and discharge cycles progress, the battery capacity may continue to increase abnormally.

[0051] The conductive layer of this invention can reduce the expansion of the core layer to less than 30%, thereby suppressing explosion and simultaneously improving battery performance. Furthermore, the conductive layer is composed of materials such as carbon, graphite, or graphene, significantly improving the conductivity of the electrode. The conductive layer can be composed of multiple layers (10 to 25 layers) to exhibit a variety of properties. The shape and structure of the silicon-carbon nanocomposite can be adjusted by controlling the reaction conditions in the reactor.

[0052] Step (c) is a step of heating and drying the silicon-carbon nanocomposite material produced above. The silicon-carbon nanocomposite material can be obtained by conventional heating and drying methods, with the heating and drying temperature being above 100°C, for example, above 100°C, above 150°C, above 200°C, above 250°C, etc. The silicon-carbon nanocomposite material has a spherical particle morphology, a particle size of less than 100 nm, and a particle size range of 10 to 50 nm. After being graded, the particles are classified by particle size for use.

[0053] In the above step (d), the vacuum heat treatment can adopt a conventional heat treatment process in the art, for example, heat treatment at 300°C to 800°C, such as 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.

[0054] Some embodiments provide negative electrode active materials, including the aforementioned silicon-carbon nanometer negative electrode active material or the silicon-carbon nanometer negative electrode active material prepared by the aforementioned preparation method.

[0055] In some embodiments, the amount of the silicon-carbon nanometer negative electrode active material added to the negative electrode active material can be a small amount, for example, 1-5%. By adding a small amount of silicon-carbon nanometer negative electrode active material, significant performance improvement can be achieved.

[0056] In some embodiments, the matrix of the negative electrode active material may be graphite or other conventional negative electrode materials.

[0057] Some embodiments provide a negative electrode comprising the aforementioned negative electrode active material.

[0058] Some embodiments provide a secondary battery, such as a lithium secondary battery, including the aforementioned negative electrode.

[0059] A lithium secondary battery includes a positive electrode, a negative electrode opposite to the positive electrode, and an electrolyte between the positive electrode and the negative electrode. The lithium secondary battery may be a lithium ion battery, a lithium ion polymer battery, or a lithium polymer battery.

[0060] As the positive electrode and the electrolyte, those commonly used in the technical field to which the present invention pertains can be used. For example, the positive electrode comprises a positive electrode active material, which may include lithium cobalt oxide LiCo 1-x M x O2 (where M is a doping element and the value of x is less than 0.5), LiMn 1-x M x O2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1), lithium nickel oxide LiNi 1-x M x O2 (where M is a doping element and the value of x is less than 0.5), nickel-cobalt-manganese ternary oxide LiNi x Co y M 1-x-y A z O2 (where M is Mn or Al, A is a doping element, and z is 0-0.1), high nickel oxide LiNi x M y O2 (where x is 0.6≤x≤0.99, and M is one or more of Co, Mn, Al, Cu, Fe, Mg, B, and Ga); lithium-rich manganese-based oxides xLi2MnO3·(1-x)LiMO2; polyanionic compounds such as lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, and fluorophosphate; vanadium oxides such as lithium vanadate, V2O5, and Cu2V2O7; x Mn 2-xLithium manganese nickel oxide having a spinel structure represented by O4; LiMn2O4, wherein part of the Li in the chemical formula may be replaced by an alkaline earth metal ion; disulfide; Fe2(MoO4)3, etc., but not limited thereto. Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, melt-type inorganic electrolytes, and the like, which are generally used in the manufacture of lithium secondary batteries.

[0061] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt. The lithium salt may be used without particular limitation, as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 may be used. The concentration of the lithium salt is preferably in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thereby exhibiting excellent electrolyte performance, and lithium ions can be efficiently transferred. In the electrolyte, in order to improve the life characteristics of the battery, suppress the reduction in the capacity of the battery, and improve the discharge capacity of the battery, in addition to the above electrolyte components, at least one additive may also be included.

[0062] Some embodiments provide a battery pack including the aforementioned secondary battery. The battery pack can be used as a power source for at least one medium-sized or large-sized device, such as a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0063] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments.

[0064] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0065] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0066] Example 1 Silicon wires are placed in a reactor containing a solvent, argon gas is injected, and a voltage of approximately 30 kV is applied to the reactor to produce silicon nanoparticles from the silicon wires. In this embodiment, the solvent is a mixture of 100 parts by weight of ethanol, 10 parts by weight of N-methyl-2-pyrrolidone (NMP), and 5 parts by weight of sorbitan monolaurate. The prepared high-energy silicon nanoparticles react with the solvent in the reactor, decomposing the solvent. The carbon component formed by the decomposition of the solvent coats the surface of the silicon nanoparticles, producing a silicon-carbon nanocomposite material. The resulting silicon-carbon nanocomposite material is then dried at a temperature above 100°C, subjected to vacuum heat treatment at approximately 700°C, pulverized, and dissociated to obtain the final product.

[0067] Figure 1 The SEM image of the silicon-carbon nanocomposite prepared in this example is shown. According to the image, it can be confirmed that the particles of the silicon-carbon composite material are spherical and the particle size is below 100 nm.

[0068] Figure 2 The TEM image of the silicon-carbon nanocomposite prepared in this embodiment is shown. According to the image combined with elemental analysis, it can be confirmed that the silicon-carbon nanocomposite material includes a core composed of silicon and a conductive layer composed of carbon coated on the core layer. The carbon layer close to the core is thicker and is an ordinary carbon or graphite layer. The multiple carbon layers outside the carbon layer are very thin and are graphene layers.

[0069] After processing the cross-sections of the silicon-carbon nanocomposite materials one by one, it was observed under high magnification that the cores of the nanosilicon balls were basically porous nanosilicon balls, some of which had 2 pores, some had 3 pores, some had 4 pores, some had 5 pores, and some had 6 pores.

[0070] Example 2 A silicon-carbon nanocomposite material was prepared in the same manner as in Example 1, except that a mixed solvent of 100 parts by weight of ethanol, 2 parts by weight of N-methyl-2-pyrrolidone (NMP) and 5 parts by weight of sorbitan monolaurate was used.

[0071] Example 3 A silicon-carbon nanocomposite material was prepared in the same manner as in Example 1, except that a mixed solvent of 100 parts by weight of ethanol, 25 parts by weight of N-methyl-2-pyrrolidone (NMP) and 5 parts by weight of sorbitan monolaurate was used.

[0072] Example 4 A silicon-carbon nanocomposite material was prepared in the same manner as in Example 1, except that 70 parts by weight of ethanol and 30 parts by weight of methanol were used instead of 100 parts by weight of ethanol.

[0073] Example 5 The silicon-carbon nanocomposite material was prepared in the same manner as in Example 1, except that 5 parts by weight of 3-methacrylate propoxytrimethoxysilane was additionally used as a solvent.

[0074] Comparative Example 1 A silicon-carbon nanocomposite material was prepared by the same method as in Example 1, except that 115 parts by weight of N-methyl-2-pyrrolidone (NMP) was used instead of the original solvent (100 parts by weight of ethanol, 10 parts by weight of N-methyl-2-pyrrolidone, and 5 parts by weight of sorbitan monolaurate).

[0075] The properties of the silicon-carbon nanocomposites prepared in the above examples and comparative examples were evaluated, and the results are listed in Table 1. The active negative electrode materials, silicon-carbon nanocomposites, carbon, and polyvinylidene fluoride (PVDF) prepared in the above examples and comparative examples were mixed to prepare a negative electrode, and then a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte was manufactured.

[0076] The capacity and initial efficiency were tested using button cells. The assembled batteries were charged and discharged in a voltage range of 2.3-4.3 V at room temperature and 0.2 C. The capacity and initial efficiency are shown in Table 1. The negative electrode expansion rate was tested using a 1 Ah pouch cell. After 100 cycles at room temperature, 3-4.2 V, and 0.2 C, the thickness change of the negative electrode was measured and the negative electrode expansion rate was calculated. The test results are shown in Table 1.

[0077] Table 1 As shown in Table 1 above, the active negative electrode materials prepared in Examples 1 to 5 exhibited excellent capacity and initial efficiency. Furthermore, tests of assembled soft-pack batteries revealed that the negative electrodes prepared using the active negative electrode materials in Examples 1 to 5 exhibited low negative electrode expansion rates, with Examples 1, 4, and 5 demonstrating the most outstanding characteristics. In contrast, the above characteristics of Comparative Example 1 were significantly inferior to those of the Examples.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. Silicon-carbon nano-negative electrode active material, characterized in that: It includes a silicon core and a conductive inhibition layer covering the silicon core; the silicon core is a nano-silicon ball, and the conductive inhibition layer is a carbon layer.

2. The silicon-carbon nanometer negative electrode active material according to claim 1, wherein: The carbon layer has a multi-layer carbon layer structure; preferably, the number of layers of the multi-layer carbon layer is 10 to 25 layers; preferably, the material of the multi-layer carbon layer is at least one of carbon, graphite, and graphene; further preferably, the material of a layer close to the core of the multi-layer carbon layer is carbon or graphite, and the remaining carbon layers are graphene layers; preferably, each carbon layer in the multi-layer carbon layer is independently a porous layer or a non-porous layer.

3. The silicon-carbon nanometer negative electrode active material according to claim 1, wherein: The particle size of the nano silicon spheres is less than 100 nm, preferably 10 to 50 nm; Preferably, the nano-silicon spheres are porous nano-silicon spheres.

4. A method for preparing a silicon-carbon nano-negative electrode active material, characterized in that: include: (a) In a reactor containing a solvent and an inert gas atmosphere, a transient high voltage exceeding 25,000 V and lasting no longer than 1 / 100 second is applied to both ends of a silicon wire. a1. Preparation of nano-silicon particles by instantaneous expansion; a2. Coating carbon on the surface of the prepared nano-silicon particles to form a silicon-carbon nanocomposite material that prevents expansion; (b) a step of classifying the silicon-carbon nanocomposite material produced above; (c) heating and drying the silicon-carbon composite material; (d) performing vacuum heat treatment on the silicon-carbon composite material; (e) A step of crushing and disintegrating the silicon-carbon composite material.

5. The method for preparing the silicon-carbon nanometer negative electrode active material according to claim 4, wherein: The solvent includes alcohol, N-methyl-2-pyrrolidone (NMP) and a first surfactant.

6. The method for preparing the silicon-carbon nano-anode active material according to claim 4, wherein: The N-methyl-2-pyrrolidone (NMP) accounts for 5-20% of the total weight of the alcohol; and the first surfactant accounts for 2-10% of the total weight of the alcohol.

7. The method for preparing the silicon-carbon nanometer negative electrode active material according to claim 5, wherein: The first surfactant is a sorbitan surfactant; The sorbitan surfactant is selected from one or more of sorbitan laurate, sorbitan palmitate, sorbitan stearate and sorbitan oleate.

8. The method for preparing the silicon-carbon nanometer negative electrode active material according to claim 5, wherein: The solvent further includes a second surfactant, which is a silane coupling agent containing an acrylate group.

9. The method for preparing the silicon-carbon nanometer negative electrode active material according to claim 8, wherein: In the alcohol, the mass ratio of ethyl alcohol to methyl alcohol is 60-80:20-40.

10. A negative electrode active material, characterized in that The invention comprises the silicon-carbon nanometer negative electrode active material according to any one of claims 1 to 3 or the silicon-carbon nanometer negative electrode active material prepared by the preparation method according to any one of claims 4 to 9.

11. A negative electrode, characterized in that The negative electrode active material according to claim 10 is included.

12. A secondary battery, characterized in that The negative electrode according to claim 11 is included.

13. A battery pack, characterized in that Comprising the secondary battery as claimed in claim 12.

Citation Information

Patent Citations

  • Silicon-carbon composite negative electrode material and manufacturing method thereof

    CN112510185A

  • System for recommending similar image based on information inserted image and method of performing the same

    KR1020250047182A